2021
DOI: 10.48550/arxiv.2109.00249
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seeing Implicit Neural Representations as Fourier Series

Abstract: Implicit Neural Representations (INR) use multilayer perceptrons to represent high-frequency functions in lowdimensional problem domains. Recently these representations achieved state-of-the-art results on tasks related to complex 3D objects and scenes. A core problem is the representation of highly detailed signals, which is tackled using networks with periodic activation functions (SIRENs) or applying Fourier mappings to the input. This work analyzes the connection between the two methods and shows that a Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Here, we explore the main properties of this definition in implicit surface reconstruction. For example, its first layer is related to a Fourier feature mapping [5], which allows us to represent high-frequency three-dimensional implicit functions.…”
Section: Neural Implicit Function Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Here, we explore the main properties of this definition in implicit surface reconstruction. For example, its first layer is related to a Fourier feature mapping [5], which allows us to represent high-frequency three-dimensional implicit functions.…”
Section: Neural Implicit Function Architecturementioning
confidence: 99%
“…The normal N i is defined by the average of the normal vectors of the faces adjacent to the vertex p i . The discrete shape operator S i at p i can be computed using Equation (5).…”
Section: Samplingmentioning
confidence: 99%
“…Evidently, sines allow the network to more accurately represent finer details. The use of sines is related to Fourier features [38], for which the aforementioned property has been theoretically explained [39] using the NTK framework [40]. We chose SIREN as our architecture due to its simplicity and effectiveness.…”
Section: Siren Representationmentioning
confidence: 99%
“…Wang et al [WLYT21] showed that the choice of the frequency of γ i biases the network to learn certain, band-width limited frequency content, where lower encoding frequencies result in blurry reconstruction, and higher encoding frequencies introduce salt-andpepper artifacts. For more stable optimization, one approach is to mask out high-frequency encoding terms at the beginning of the optimization, and progressively increase the high-frequency encoding weights in a coarse-to-fine manner [LMTL21,BHumRZ21]. SAPE proposed a more sophisticate masking scheme [HPG * 21], which also allowed the encoding of spatially varying weights.…”
Section: Overcoming Spectral Biasmentioning
confidence: 99%